Análisis de los modelos de factibilidad financieros de proyectos de vivienda de interés social con estrategias certificadas de sostenibilidad (2020)
Social interest housing is booming in Colombia because it is of great importance for the economic and social development of the country, in that sense the sustainability of such projects takes on greater relevance, as a fundamental pillar of all this development and is therefore necessary To encourage it through public and credit policies that accelerate its implementation, the purpose of this degree project is to study how incentives such as reduction in the construction credit rate and expansion of the financed amount act in financial models, through study cases.